(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Preterm lung is fragile and deficient of surfactant, which is why most preterms suffer from respiratory distress syndrome. Administration of antenatal steroids and use of exogenous surfactant has played a very important role in decreasing the incidence of mortality and morbidity in preterm infants. The commonest route of administration of exogenous surfactant is through the endotrechial tube post intubation. But, due to increased popularity of non invasive ventilation in both term and preterm infants, various other methods of surfactant administration has come into light. Through this review we will try to throw some light on different ways through which surfactant administration can be done in preterm neonates.